Tour guides performance in Malaysia : application of the importance performance analysis - Khalifah, Zainab (2007)
As tourism becomes an important industry in Malaysia, there is an increasing need for tour guides, not only in terms of their numbers, but also the ability to deliver a quality service. This paper will discuss the findings of a study carried out to determine the service quality of tour guides in Malaysia using the Importance-Performance Analysis (IPA). The study adopted a quantitative and descriptive approach, focusing on the service quality of tourist guides from the perspective of the tourists. The main aim of this approach is to identify the gaps in the actual delivery as compared to the expectations of the tourists, based on a list of 20 attributes. In all service quality attributes the performance of guides were lower than the importance placed on the service quality attributes by tourists. The biggest gaps were introducing tourists to reliable shops, inform safety regulations, punctual, honest & trustworthy, responsible, sense of humour and inform visitors about destination customs. Based on the findings, a number of issues were identified and discussed.